Penerapan Mesin Oven Hemat Energi Untuk Pengeringan Brown Sugar pada Kelompok Wanita Tani Rahayu Manunggal Desa Ngancar Di Kecamatan Candimulyo Kabupaten Magelang - Suroto Munahar; Bagiyo Condro Purnomo; Budi Waluyo; Saifudin Saifudin (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
This article is the result of implementing the CSR program of PT PLN Magelang Regency branch to help solve problems in the Rahayu Manunggal Women Farmers Group (KWT). High production costs and low profits are obstacles faced by KWT Rahayu Manunggal. This problem is caused by the production process of making brown sugar which uses quite a lot of energy, including the drying process of brown sugar. Applying an energy-efficient oven at KWT Rahayu Manunggal can help overcome this problem. The concept of the oven machine is designed by utilizing the heat/energy stored in the exhaust gas produced by the sap cooking furnace. The results obtained from this system can increase profits and reduce production costs, as well as improve the cleanliness of brown sugar processing.